Bullying Prevention Strategies Through School Capacity Building (SCB) in Integrated Islamic Schools to Support the Sustainable Development Goals (SDGs) - Irman Suherman; Abraham Yazdi Martin; Imam Kurniawan; Asep Thobibudin Qolyubi; Radif Khotamir Rusli; Lise Purnamasari (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Bullying in educational institutions is a critical issue that affects students’ well-being and academic performance, necessitating effective prevention strategies. This study develops a bullying prevention strategy through school capacity building (SCB) in Integrated Islamic Schools to support the Sustainable Development Goals (SDGs). A qualitative approach with a case study method was employed to explore the underlying causes of bullying and to formulate effective prevention strategies through SCB. The findings revealed three key themes, the role of school policies in preventing bullying; leadership models for preventing bullying; and the involvement of teachers and parents in fostering a bullying-free environment. The research highlights that a comprehensive approach, integrating structured school policies, strong leadership, and active participation from teachers and parents, is essential for effective bullying prevention. The study emphasizes that sustainable development cannot be realized without peace, and peace cannot be sustained without the development of quality education. This research contributes to the improvement of Islamic education by promoting a safe, inclusive, and supportive environment, which is essential for fostering future leaders and ensuring the advancement of global peace.